1979
DOI: 10.1063/1.327000
|View full text |Cite
|
Sign up to set email alerts
|

Crystal orientation and its formation process of an anisotropic Mn-Al-C permanent magnet

Abstract: An easy axis distribution and a crystal texture in a warm extruded anisotropic Mn-AI-C magnet were determined by X-ray diffraction analyses. Resulting values in (001) pole density are treated by introducing a normalization condition in order to determine the quantitative values. The distribution is expressed only as a function of tilt angle 4>. and is found to consist of the following Gaussian distribution term and constant. P(4)) = 3.42 exp [-4>2/(2X30.8 2 ) 1 + 0.11. Magnetically measured Mr/Ms = 0.88 is sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This was a result of the ε-τ solid-phase transformation. The ε-τ transformation was reported to be a massive transformation 33) . During the massive transformation, ε-phase with disordered hcp structure became ordered hcp structure, following the hcp-L1 0 transformation.…”
Section: Discussionmentioning
confidence: 99%
“…This was a result of the ε-τ solid-phase transformation. The ε-τ transformation was reported to be a massive transformation 33) . During the massive transformation, ε-phase with disordered hcp structure became ordered hcp structure, following the hcp-L1 0 transformation.…”
Section: Discussionmentioning
confidence: 99%
“…19 The tp for the hot-deformed magnet is calculated to be 0.26 and the texture developed is in the plane perpendicular to the deformation direction. In the case of Mn-Al-C magnets prepared by extrusion, Koch et al, 1 Ohtani et al, 4 Sakamoto et al 20 and Bittner et al 19 reported texture formation in the axis parallel to the extrusion direction. Figure 4 shows the XRD patterns of the magnets prepared by the three processes.…”
Section: Resultsmentioning
confidence: 99%
“…This manifests that during the HD process, the grains tend to form a concentrated orientation relationship while forming the texture, and this orientation relationship is related to the mechanism of the texture formation of the grain rotation and recrystallization. [19][20][21][22] The results of XRD, EBSD, and misorientation analysis consistently show that the increase in deformation can promote the formation of (001) texture. Good (001) texture is primary for the permanent magnet materials to improve remanence.…”
Section: Resultsmentioning
confidence: 85%